2019
DOI: 10.1002/cam4.1531
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjuvant radiotherapy for atypical and anaplastic meningioma

Abstract: The effect of adjuvant radiotherapy in management for high‐grade meningiomas, especially atypical meningiomas, remains controversial. We aimed to explore the role of adjuvant radiotherapy in this population. A total of 162 adults with high‐grade meningiomas (99 atypical meningiomas and 63 anaplastic meningiomas) were treated from 2003 to 2008 at Huashan Hospital. One hundred and seventeen patients presented with primary and 45 with recurrent disease. One hundred and fifteen patients (70.9%) were treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 26 publications
3
35
3
2
Order By: Relevance
“…Hilary et al demonstrated that adjuvant radiotherapy for meningiomas resected with Simpson grade I-III improved local control rates [16]. The prognosis of primary anaplastic meningiomas has been shown to be improved by adjuvant radiotherapy; however, in the subgroup analyses, no significant improvement was observed in either PFS or OS in patients with recurrent meningiomas [17]. In the present study, radiotherapy did not improve PFS and OS for overall patients.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Hilary et al demonstrated that adjuvant radiotherapy for meningiomas resected with Simpson grade I-III improved local control rates [16]. The prognosis of primary anaplastic meningiomas has been shown to be improved by adjuvant radiotherapy; however, in the subgroup analyses, no significant improvement was observed in either PFS or OS in patients with recurrent meningiomas [17]. In the present study, radiotherapy did not improve PFS and OS for overall patients.…”
Section: Discussioncontrasting
confidence: 54%
“…In the recent decade, the efficacy of adjuvant radiotherapy has been demonstrated for high-grade meningiomas [15][16][17]. Hilary et al demonstrated that adjuvant radiotherapy for meningiomas resected with Simpson grade I-III improved local control rates [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After surgery, radiation is usually used as adjuvant therapy at many institutions for patients with grade III meningiomas (even after GTR) and incompletely resected grade II meningiomas [7]. It has been reported that GTR and adjuvant radiation were associated with improved local control of the tumor [5, 9, 10]. However, the long-term impacts of GTR and radiotherapy for patients’ survival are still unclear, even on the modern management of high-grade meningiomas according to the adapted WHO diagnostic criteria (WHO 2000/2007 editions) [2, 7].…”
Section: Introductionmentioning
confidence: 99%